Molecular Basis of CYP2B2 Induction - Horley, Neill (1999)
Many structurally unrelated chemicals can induce members of the cytochrome P450 superfamily with phenobarbital (PB) being a typical example. PB induces CYP2B1/2, which are most highly expressed in the liver. Their mechanism of activation has not yet been elucidated, with advances hampered by the absence of a suitable cell culture system to mimic the in vivo PB-mediated induction. During this thesis a primary rat hepatocyte culture system has been developed which is highly responsive to PB at both RNA and protein levels. A sensitive and specific RNAse protection assay (RPA) has been used to demonstrate that CYP2B2 mRNA is highly inducible in vitro by PB. This response occurs in a time and dose-dependent manner. The use of RPA and Western blotting has demonstrated that this primary rat hepatocyte culture system supports the induction of CYP2B2 mRNA and protein levels by PB. Sequencing -1.4kb of the 5' flanking region of the CYP2B2 gene identified genomic regulatory elements and highlighted the location of the phenobarbital response element (PBRE). The PBRE was sub-cloned into various reporter constructs and transfection technology was used to determine its PB-mediated induction. A comparative study of the constructs generated in this thesis to that of a construct provided by Anderson's group (Trottier et al., 1995) was undertaken and no differences were found in their PB-responsiveness. The Anderson construct containing the PBRE was shown here to confer a 3.3-fold PB-mediated induction of the CYP2B2 gene by CAT reporter assays. This induction was shown to be both dose and time dependent. The induction is lower than that obtained by other workers due primarily to assay conditions which were not yet optimal. However, the effects of androstane on the constitutively active receptor (CAR) may also play a role in the small inductive response of the phenobarbital response element to PB.